Development of Virtual Learning using Problem-Based Learning Models for Vocational Education Students - Doni Tri Putra Yanto; Maryatun Kabatiah; Hermi Zaswita; Giatman Giatman; Hansi Effendi (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2022)
This study discusses efforts to improve the implementation of remote learning that is not optimal through the development of Virtual Learning using the Problem-Based Learning Model for vocational education students in the learning process of Electrical Lighting Installation at Vocational High School (SMKN) 2 Lubuk Basung, Sumatera Barat Province. The emergence of the Covid-19 pandemic demands a rapid change in the implementation of learning from face-to-face learning in the classroom to remote learning. This change requires innovations in implementing learning such as media and learning models to ensure optimal learning implementation even though it is carried out remotely. The 4-D development model (Four-D) is applied in this study as a research product development model consisting of 4 stages: Define, Design, Develop, and Disseminate. The instrument used for data collection in the study is a questionnaire for the validity and practicality assessment instrument. The results showed that the virtual learning developed using the Problem-Based Learning Model was valid to be applied in the learning process. After being tested in the learning process, the Virtual Learning developed has been practically used in the learning process to optimize the implementation of learning and improve student learning outcomes. It can be concluded that the Virtual Learning developed with the Problem-Based Learning Model is valid and practical to use in the learning process to optimize the implementation of electric lighting installation learning for vocational education students.